2013
DOI: 10.4274/turkderm.72623
|View full text |Cite
|
Sign up to set email alerts
|

Besinlerle Yapılan Atopi Yama Testinin SCORAD İle İlişkisi

Abstract: Türk derm-De ri Has ta lık la rı ve Fren gi Ar şi vi Der gi si, Ga le nos Ya yı ne vi ta ra f›n dan ba s›l m›fl t›r. Turk derm-Arc hi ves of the Tur kish Der ma to logy and Ve ne ro logy, pub lis hed by Ga le nos Pub lis hing. ÖzetAmaç: Besinlerle atopik dermatit (AD) kliniği arasındaki ilişki tartışmalıdır.Besinlerle yapılan "fresh prick testleri"nin (FPT) özgünlüğünün düşük olması, AD'de çoğunlukla lezyonların geç ortaya çıkması ve buna bağlı anamnezdeki tutarsızlıklar, provokasyon testinin zaman alıcı ve ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…In this study, no relation was observed between SCORAD index and prick test positivity, total IgE, and serum eosinophil count. 16 These results were similar to our results. In a study in which 236 patients with AD were examined, food allergen sensitization was positive in 31% of patients, and the most common food allergies were found against egg, cow's milk, and peanuts.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, no relation was observed between SCORAD index and prick test positivity, total IgE, and serum eosinophil count. 16 These results were similar to our results. In a study in which 236 patients with AD were examined, food allergen sensitization was positive in 31% of patients, and the most common food allergies were found against egg, cow's milk, and peanuts.…”
Section: Discussionsupporting
confidence: 93%
“…• No significant correlation was found between the severity of AD and food allergy and laboratory tests. Severe AD was found to be 24.2% (16). In our study, the rate of FLG mutations was found to be 1.51%.…”
Section: Main Pointssupporting
confidence: 48%
“…Aeroallergens are also one of the AD triggers and include indoor aeroallergens such as house dust mite (HDM), pet dander, fur, cockroach, and mold, and outdoor aeroallergens such as tree, grass, and weed pollen (Werfel et al, 2015;Chong et al, 2022). HDM is a common sensitizing factor in pediatric AD patients and it has been also reported that children with a strong skin prick test reaction to HDM have more severe disease (Kutlu et al, 2013).…”
Section: The Environmental Factors Associated With Admentioning
confidence: 99%